The Experience of Families who Care for Relatives with Mental Disorders Post Arbitrary Coercion: A Qualitative Study - Mubin, Mohammad Fatkhul; Rahayu, Desi Ariyana; Dhamanik, Reina; Hsieh, Chia-Jung; Basuki, Rochman (Fakultas Ilmu-ilmu Kesehatan, 2023)
People with mental disorders who experience coercion and are referred to a mental hospital are often shackled after returning from the hospital or re-admitted to the mental hospital. However, some families take care of their family members with mental illness who had previously been coerced. The time taken to care for relatives with mental disorders at home is crucial as caregivers of relatives with schizophrenia and early psychosis experience significant stress and psychosocial burden. Meanwhile, the family members are supposed to maintain their relative’s condition to avoid relapse. This study explores the experiences of families who cared for their relatives with mental disorders who experienced coercion to give insight and information to patients, families, and communities. This is a phenomenological qualitative study. The sampling technique used was purposive sampling, with the number of participants being 11 family members who treated their relative suffering from mental illness post-coercion. The descriptive analysis resulted in 5 themes: 1) Heavy burden, 2) Family support, 3) Gratitude, 4) Adjustment, and 5) Improved mental health condition. The results of this study can be used as a reference for helping families with the psychological and physical treatment of their post-coercion relatives.